Design and analysis of a piezoelectric energy harvester for rotational motion system. (1st March 2016) - Guan, Mingjie; Liao, Wei-Hsin
Highlights: A novel design of rotational piezoelectric energy harvester is presented. The rotational energy harvesting system is modeled. The harvester can generate a high voltage at a low rotating frequency of 1.2 Hz. The harvester can generate a high output power in a wide rotating frequency range. Power output of 83.5–825 μW is obtained at rotating frequencies of 7–13.5 Hz. Abstract: This paper presents a piezoelectric energy harvester for rotational motion applications. The piezoelectric energy harvester is mounted on a rotating system in which the axis of rotation is more or less parallel to the Earth's surface. As the harvester rotates, the piezoelectric elements in the energy harvester are repeatedly deformed to generate electrical power. A novel design of the harvesting structure is proposed in this paper and analyzed theoretically. Experiments were conducted to validate the concept and analysis. Power output of 83.5 – 825 μW is achieved at the rotating frequencies of 7 – 13.5 Hz with a prototype of rotational energy harvester. Results show that the harvester can offer sufficient power for low-power wireless transmitters.